A Program to Support Kindergarten Teachers in Handwriting Instruction. Issue 2 (2nd April 2020) - Nye, Jill Ann; Sood, Divya
ABSTRACT: Background : This study was designed to develop a program to increase the confidence level among kindergarten teachers to teach handwriting in kindergarten. Methods : A pretest-posttest quasi-experimental research design was utilized. Five teachers employed at the kindergarten center in a school district in Illinois participated in the study. Data were collected pre and post-program participation on teacher's ability to generate strategies to support the handwriting needs of kindergarten students. Data were also collected to teachers' confidence level in teaching handwriting pre and post participation. Results : Five teachers participated in this program. The results of this study revealed changes in teachers' perceived level of confidence to teach handwriting skills. Teachers also reported enhancement of knowledge related to foundational skills and developmental progression related to teaching handwriting in kindergarten as a result of participation in the program. Conclusion : Occupational therapists in the school setting can provide support to teachers in meeting the challenge of providing handwriting instruction at the kindergarten level despite the fact that they may not have sufficient knowledge related to child development or the development of foundational skills that impact the acquisition of handwriting skills. Occupational therapists in the school setting bring a unique skill set that can assist teachers in expanding their knowledge base in this area to enhance their teaching practices and gain an understanding of foundational skills needed for success in handwriting. Additionally, through collaboration and education, the occupational therapist can enhance knowledge and ability to generate strategies to assist struggling students while introducing an element of "play" into the process.